2015
DOI: 10.1177/0272989x15576487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Graphical and Numerical Likelihood Formats on Perception of Likelihood and Choice

Abstract: Perception of likelihood differs significantly depending on the numerical format used. The 1-in-X format yields higher perceived likelihoods and it appears to be the easiest format to interpret. Graphs primarily affect perception of likelihood of people with lower numerical aptitude. These effects should be taken into account when discussing medical risks with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 57 publications
9
53
0
Order By: Relevance
“…While the effect was smaller for the numerical scales, it was reliable, being directionally replicated across the four experiments featuring a numerical scale, and detected as significant in a meta-analysis. This finding thus replicates and extends the prior research on the "1-in-X" effect (Oudhoff & Timmermans, 2015;Pighin et al, 2011;Sirota et al, 2014b). It is also consistent with the findings that responses provided on numerical scales are less prone to biases than on verbal ones (Windschitl & Weber, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…While the effect was smaller for the numerical scales, it was reliable, being directionally replicated across the four experiments featuring a numerical scale, and detected as significant in a meta-analysis. This finding thus replicates and extends the prior research on the "1-in-X" effect (Oudhoff & Timmermans, 2015;Pighin et al, 2011;Sirota et al, 2014b). It is also consistent with the findings that responses provided on numerical scales are less prone to biases than on verbal ones (Windschitl & Weber, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Precisely how an individual's personalized risk resulting from an online risk calculator should be communicated has become a crucial question . Although some risk formats (eg natural frequencies and some graphical formats in addition to numerical information) in general seem to evoke better risk understanding than other formats (eg percentages only), it remains unclear how the provided risk information supports an individual's understanding of their risk. Previous user tests have shown that risks presented as percentages in risk calculators often have unclear or ambiguous meaning for end‐users, even when accompanied by graphical information .…”
Section: Introductionmentioning
confidence: 99%
“…Other more general problems revealed by such user tests are that the risk message does not necessarily match the individual's existing beliefs and expectations about risk factors, and that, perhaps partly as a result of this, many end‐users with relatively high risks tend to undervalue or normalize their risk . Such problems are particularly urgent as many people, not only those with lower educational levels, have poor health literacy and numeracy skills, thereby placing them at a higher risk of misinterpreting information and making non‐informed decisions . It is therefore important to investigate how end‐users of risk calculators make sense of their risk result and to improve risk communication accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate understanding of these risks is necessary because the risks typically come with associated benefits, and people need to be able to determine if the risks are worth the potential benefits. To assist people in these tasks, experts often communicate the risk information to relevant decision makers (Fagerlin, Zikmund‐Fisher, & Ubel, ; Feldman‐Stewart, Kocovski, McConnell, Brundage, & Mackillop, ; Fischhoff, ; Lipkus, ; Oudhoff & Timmermans, ; Visschers, Meertens, Passchier, & de Vries, ). Unfortunately, communicating the likelihood that a risky event will occur is challenging.…”
mentioning
confidence: 99%